Infectious endocarditis: rlieumatologic aspects - G M Tarasova; B S Belov; K M Balabanova (Научно-практическая ревматология, 2008)
Objective. To assess rheumatologic aspects of modern infectious endocarditis (IE) and to determine role of anti-inflammatory therapy in complex treatment of the disease. Material and methods. 50 pts with IE (24 female, 26 male aged 16 to 60 years were included). Primary IE was diagnosed in 15, secondary - in 35 cases. 7 pts had acute and 43 — subacute course. 40 pts had definite and 10 — probable IE. Results. Mean period till correct diagnosis establishment was 112± 116,5 days. Diagnostic difficulties were more frequent in subacute variant of IE (p=0,03). Heart diseases prevailed among cardiac risk factors (p=0,0l). Clinical picture of IE was very polymorphous. Glucocorticoids (GC) were administered to 21 pts in addition to antibiotics due to signs of organ immunopatology and high laboratory measures of immune activity. Positive effect of glucocorticoids was achieved in 64% of pts. Conclusion. Development of immunological changes complicates timely diagnosis of IE and requires exclusion of different diseases including rheumatic pathology. IE treatment strategy does not exclude administration of GC low doses for prominent immunopathological signs in addition to massive antibacterial therapy.